"Pericardial flare" associated with immunoglobulin G4-related disease: A case report - rapid transition from cardiac tamponade to effusive constrictive pericarditis. Issue 1 (July 2021) - Fujita, Hiroshi; Matsumoto, Kensuke; Miwa, Keisuke; Hirata, Ken-ichi
Abstract: Immunoglobulin G4-related disease (IgG4-RD) has recently been recognized as a systemic fibroinflammatory disease characterized by IgG4-positive lymphoplasmacytic infiltration. Despite the increased awareness of this disease category, cardiovascular involvement has rarely been reported. An 83-year-old man was admitted because of a moderate amount of pericardial effusion concomitant with bilateral pleural effusion. Despite aggressive heart failure therapy, pericardial effusion increased. He underwent pericardial drainage, and heart failure symptoms significantly improved. After only 1 month, right-sided heart failure with re-accumulation of pericardial fluid recurred, although the results of cardiac catheter examination were not indicative of constrictive pericarditis. Despite the aggressive medication, he developed weight gain and pleural effusion 6 months after pericardial drainage. Based on multimodal hemodynamic and morphological evaluations, he was finally diagnosed with effusive constrictive pericarditis and underwent total pericardiectomy. Based on histopathological findings, the final diagnosis was established as IgG4-RD associated constrictive pericarditis. We report an extremely rare case of IgG4-RD associated pericardial involvement, in which rapid transition from cardiac tamponade to effusive constrictive pericarditis was confirmed. Diagnostic work-up for constrictive pericarditis requires a high index of suspicion. Increased recognition of IgG4-RD associated pericardial involvement could potentially mitigate morbidity and might contribute to improved patient outcomes. <Learning objective: Immunoglobulin G4-related disease (IgG4-RD) is a systemic inflammatory disease characterized by chronic IgG4-positive lymphocyte infiltration that causes fibrosclerotic changes in various tissues and organs. Detailed serial multimodal imaging and physical examination contribute to the recognition of latent constrictive physiology and clinical decision-making. Increased recognition of IgG4-RD associated pericardial involvement could lead to early diagnosis and might contribute to improved patient outcomes.>